Understanding fluorometric interactions in ion-responsive sustainable polymer nanocomposite scaffolds. Issue 37 (1st September 2020) - Janghela, Shriram; Devi, Sudeepa; Kambo, Neelu; Roy, Debmalya; Eswara Prasad, N.
Abstract : Variation in the fluorescence intensity of sustainable porous scaffolds by interaction with analytes to remotely monitor the decontamination efficiency. Abstract : The fluorescent colour in biodegradable and biocompatible flexible polymer nanocomposite gels was modulated in order to gain insight into the interfacial interactions of functional scaffolds with metal ions. The hybrid nanomaterials were introduced into the polymer matrix to obtain mechanically robust porous morphologies where the intrinsic luminescence matrix was found to critically enhance the threshold of the visual detection limits. The quenching of fluorescence intensity has been predominantly attributed to the interactions of functional receptors of luminescent nanofillers with respect to the chromophores of the fluorescent matrix. The chromium ion is selected to understand the change in fluorescence intensity of the nanocomposite gel with the degree of metal ion adsorption. The number of functional nanomaterials loaded into the matrix and the luminescence nature of the base polymer are varied with the purpose of gaining insight into the remote sensing mechanism of the colorimetric fluorescent probe.